(1497) A model for distribution of resources in multi-projects نموذج لتوزيع الموارد في المشاريع المتعددة - Abdel Rahman, Yehia (The Institute of National Planning, 2018)
One of the common problems which faces a production or a construction firm, is to distribute its resources on its different projects. There will be no problem, if the resources were enough to cover the needs of all projecie. The problem will arlaee, if one project or more cauld not be accomplished at its exact time. In this case, some subsidiary problems could be created.